Perceptions of professionalism: practitioner reflections on the state of Australian public relations - Wolf, Katharina; De Bussy, Nigel (Deakin University Australia, 2008)
This paper highlights Australian public relations practitioners? perceptions of the current state of their profession, based on a study conducted in late 2007/early 2008. Approximately half the respondents were non-members of the Public Relations Institute of Australia (PRIA), indicating that the representativeness of the peak professional body remains at best questionable. This has implications for standards of practice, compliance with codes of ethics (Bowen, 2007) and, ultimately, the professionalisation of the field. Despite global efforts by professional associations to develop the public relations body of knowledge, enforce higher ethical standards, and encourage certification and accreditation ? the three defining characteristics of a profession (Cutlip, Center, & Broom, 2006; Grunig & Hunt, 1984) ? research results indicate that public relations in Australia continues to be regarded as a ?semi-profession? (Dozier, 1992). Despite seeing some improvements, respondents reported a continued need to educate employers, management and the general public about the roles and responsibilities of public relations. Concerns were also raised about the ability of professional bodies ? specifically the PRIA - to handle ethical issues and misconduct, in order to protect the standing and reputation of the field.